Multicast QoS Routing Using Collaborative Path Exploration - Singh, Jaipal (IEEE Computer Society, 2010)
Quality of Service (QoS) is one of the most active research areas in networking. The most fundamental requirement for QoS routing is the ability to find and maintain a network path that provides the required network resources between two or more nodes. In this paper, we present a distributed collaborative multicast QoS routing architecture that uses a semi-greedy probing heuristic to quickly find a QoS path between a joining node and the multicast tree. The proposed architecture will enable the routers along the path to intelligently and dynamically discover a QoS path. Any router that receives a probe will only know its neighbours and it will create a link to the previous router from where the probe comes from. The proposed architecture is a tree-initiated QoS search and the first QoS packet to reach the joining node will be used as the QoS path. Analysis of this method shows that the path search time and message overhead is lower than other similar schemes.